2014
DOI: 10.1002/dvdy.24209
|View full text |Cite
|
Sign up to set email alerts
|

carbamoyl‐phosphate synthetase 2, aspartate transcarbamylase, and dihydroorotase (cad) regulates Notch signaling and vascular development in zebrafish

Abstract: Background: The interplay between Notch and Vegf signaling regulates angiogenesis in the embryo. Notch signaling limits the responsiveness of endothelial cells to Vegf to control sprouting. Despite the importance of this regulatory relationship, much remains to be understood about extrinsic factors that modulate the pathway. Results: During a forward genetic screen for novel regulators of lymphangiogenesis, we isolated a mutant with reduced lymphatic vessel development. This mutant also exhibited hyperbranchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Whole-mount in situ hybridisation in zebrafish larvae was performed as described (Coxam et al, 2015;Duong et al, 2014). Section and whole-mount in situ hybridisation in mouse was performed as described (Metzis et al, 2013;Fowles et al, 2003).…”
Section: In Situ Hybridisation and Immunofluorescence Stainingmentioning
confidence: 99%
“…Whole-mount in situ hybridisation in zebrafish larvae was performed as described (Coxam et al, 2015;Duong et al, 2014). Section and whole-mount in situ hybridisation in mouse was performed as described (Metzis et al, 2013;Fowles et al, 2003).…”
Section: In Situ Hybridisation and Immunofluorescence Stainingmentioning
confidence: 99%
“…S4A–C). Alternatively, recent work has suggested that SPARC may promote solubility of Col IV in the extracellular space (Pastor-Pareja and Xu, 2011; Shahab et al, 2015). In Drosophila larvae, Col IV is produced by the fat body and then distributed, via the hemolymph, to organs throughout the body.…”
Section: Resultsmentioning
confidence: 99%
“…The fat body itself is surrounded by a BM; thus, the Col IV produced by this organ must remain soluble in order to pass through this BM and diffuse to distant sites. Loss of SPARC in this system causes Col IV to accumulate around fat body cells in a cell-autonomous manner (Pastor-Pareja and Xu, 2011; Shahab et al, 2015). In contrast, Col IV produced by the follicle cells is meant to integrate into the adjacent BM immediately upon secretion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As ISH is insensitive at later developmental stages, we examined mafba expression in FACS (fluorescent-activated cell sorting)-sorted populations of arterial ECs (AECs), venous ECs (VECs), and LECs that we isolated from 60 hpf, 3 dpf, and 5 dpf embryos (Fig. 3B,C;Coxam et al 2014Coxam et al , 2015. Indicative of lineage-restricted expression in the vasculature, we found that mafba was highly enriched in VECs compared with AECs at early time points (comparable with known VEC markers) and was enriched in LECs compared with VECs by 5 dpf (comparable with known venous and lymphatic markers lyve1b and prox1a).…”
Section: Mafba Is Expressed In the Pcv And Enriched In Secondary Sproutsmentioning
confidence: 99%